Endocrine response to high intensity barbell squats performed with constant movement tempo and variable training volume - Wilk, Michal; Petr, Miroslav; Krzysztofik, Michal; Zajac, Adam; Stastny, Petr (Neuro endocrinology letters, 2018)
OBJECTIVE: Research indicates that among the many elements of resistance exercise protocols, training volume and total training load are the key factors for post-exercise increase in the secretion of testosterone (T), growth hormone (GH), insulin-like growth factor (IGF-1) and cortisol (C). The aim of this study was to determine the effects of resistance exercises with variable volume and constant intensity and movement tempo on post-exercise concentrations of selected anabolic and catabolic hormones. MATERIALS AND METHODS: 28 experienced powerlifters (27.8 ± 2.9 years, with 6.64 ± 1.29 years of training experience, average body mass of 85.3 ± 3.3 kg and body height of 165.8 ± 10.3 cm) who compete at the national and international level performed three repetitions of barbell squats with a constant external load of 90% 1RM and variable volume (3, 6 and 12 sets of squats) in three stages (pre-exercise, immediately post exercise, and 1h after exercise) over three consecutive weeks. Venous blood samples (10ml) were collected from the antecubital vein, to determine pre- and post-exercise values of the following variables T, GH, IGF-1, C, at rest, immediately after the cessation of the last set of squats, and after 60 minutes of recovery. RESULTS: The T test showed that performing 6 and 12 sets resulted in increases of post exercise GH (p<0.01). Performing 6 sets of squats resulted in post exercise decrease (p<0.01) in IGF-1 and C. Performing 3 sets of squats resulted in immediate post exercise decrease of IGF-1 (p<0.01), which was not maintained 1h after exercise. There were no other significant differences in analysed variables, with the training volume of three sets of three repetitions, confirming previous data suggesting that low volume is the limiting factor in increased post-exercise secretion. CONCLUSION: This study demonstrated that in terms of endocrine response, the optimal volume of high intensity strength exercise is six sets. Therefore, intentionally high volume (12 sets) or low volume (3 sets) are not an effective stimuli for endocrine responses of trained individuals. The 6 sets of squats seems to drive hormonal responses of GH, C and IGF-1, which may play a significant role in stimulating muscle growth and tissue regeneration.
Keywords: Insulin-Like Growth Factor I; Resistance Training; Weight Lifting; Cross-Sectional Studies; lidský růstový hormon; Time Factors; Human Growth Hormone; mužské pohlaví; Testosterone; průřezové studie; Adult; vzpírání; testosteron; hydrokortison; odporový trénink; Hydrocortisone; Humans; časové faktory; dospělí; lidé; Male; insulinu podobný růstový faktor I